Educação em sexualidades crítica : formação continuada de professoras (es) com fundamentos na pedagogia histórico-crítica - Biancon, Mateus Luiz (2016)
Based on theoretical matrix that considers education as an element of social transformation, this research seeks the possibility of confronting the normative, non-historical, non-critical and homonegative understanding in a dialectical exercise through formative action in Critical Sexualities Education. In this context, the aim of this study, as a proposal of a formative process was to know the required elements of social practice of the participants of this research in order to promote changes in matters related to education, more specifically, gender issues and sexuality in public schools. Thus, this qualitative descriptive research grounded on the foundations of historical-critical pedagogy, whose basis consists of the historical dialectical materialist method. We seek to understand the concrete reality of the educator who deals with sexuality as his/her educational praxis, which resulted in an analysis of the educational work, as an investigative praxis, emphasizing the importance of historical dialectical materialism for scientific advancement. In the development of this study, we formed a group of 22 teachers from Elementary School - final years - and High School, which allowed the structuring of a set of strategies, which enabled educational actions and critical thinking, culminating in a continued training in Critical Sexualities Education, based on the Historical-Critical Pedagogy. The results of this educational process revealed the need to reflect on the reality of public educational policies, the work and autonomy of the teacher through appropriation and ability to interpret reality according to the socialist political conception; also, the historical-critical pedagogical conception of hegemonic ways of conceiving the educational work and the topic of gender and sexuality in education. Likewise, the qualitative research met the methodological issues required for the interpretation of concrete reality. From the results of the present study, we concluded that the critical formative process can elucidate the present conflicts found in schools, providing a reflexive action that transforms the way of thinking and acting. Through such actions, the participants of the formative process can assume the role of social transformers, being aware of their political and emancipatory role in combating domination and alienations that individuals are liable to, being divided into economical, ethnic, gender and sexuality classes.